PERAN DAN TANGGUNG JAWAB BANK DALAM MENGATASI TINDAK KEJAHATAN PENCUCIAN UANG - Yustia Okta Pradini; Fauzan Azima Faturachman; Maudy Anjani; Kinayah Ashifa; Farahdinny Siswajanthy (JURNAL ILMIAH NUSANTARA, 2024)
Money laundering is one of the serious crimes that can threaten economic stability and the integrity of the financial system. This article was created with the aim of analyzing the role and responsibility of banks in dealing with money laundering crimes, focusing on legal regulations and practices applied in Indonesia. This research was conducted using a normative juridical research methodology by investigating various laws and regulations that apply in Indonesia. The results of the study show that banks have roles and responsibilities and are required to apply principles in efforts to prevent money laundering crimes. In addition, banks also have an obligation to ensure that all staff have received adequate training on money laundering prevention.